The Role of Interoperability in Construction Projects. Communication and the Implementation of CoClass. - Safdari, Hamed; Zayton, Hedro (My University, 2018)
This report presents the role of the interoperability in construction projects. Bad communication leads to projects losing both time and money. Communication and classifications are essential aspects of the construction projects. Therefore, the implementation of the new classification CoClass becomes an interesting subject. Study have shown that the previous classification BSAB 96 has some limitations. The classification does not support the entire project lifecycle and is not developed for implementation with today's modern technology. Therefore, there is a demand to improve the classifications. CoClass is intended to be an improved classification for the construction industry in Sweden. Accordingly, the aim of this study is to look into the implementation of CoClass. The report uses the method of qualitative research. The chapter, Framework of understanding explains in depth the two classifications. The case study investigates Västlänken and the sub-project Centralen. Centralen is working with CoClass and the empirical data is based on interviews conducted and analysed. The conclusion is that proper communication is important and to use a common language is vital. In the project Västlänken, CoClass have been implemented and no problems have occurred in the transition to the production phase. Trafikverket is confident in the ability of CoClass in regards of the implementation in the entire project lifecycle. Moreover, it is highlighted that the construction industry in Sweden is not communicating well. Improvements are essential in this area. With the implementation of CoClass the ability to communicate properly is a factor that might lead to successful projects with the results of saving both time and money. In the comparison between CoClass and BSAB 96 the most important improvements with CoClass are highlighted. CoClass have shown to be an improvement over BSAB 96. It covers more of the project lifecycle. CoClass together with some software programs will aid the projects and the use of BIM.
Keywords: Samhällsbyggnadsteknik; Civil Engineering